GABA maintains the proliferation of progenitors in the developing chick ciliary marginal zone and non-pigmented ciliary epithelium. - Henrik Ring (Public Library of Science (PLoS), 2012)
GABA is more than the main inhibitory neurotransmitter found in the adult CNS. Several studies have shown that GABA regulates the proliferation of progenitor and stem cells. This work examined the effects of the GABA(A) receptor system on the proliferation of retinal progenitors and non-pigmented ciliary epithelial (NPE) cells. qRT-PCR and whole-cell patch-clamp electrophysiology were used to characterize the GABA(A) receptor system. To quantify the effects on proliferation by GABA(A) receptor agonists and antagonists, incorporation of thymidine analogues was used. The results showed that the NPE cells express functional extrasynaptic GABA(A) receptors with tonic properties and that low concentration of GABA is required for a baseline level of proliferation. Antagonists of the GABA(A) receptors decreased the proliferation of dissociated E12 NPE cells. Bicuculline also had effects on progenitor cell proliferation in intact E8 and E12 developing retina. The NPE cells had low levels of the Cl-transporter KCC2 compared to the mature retina, suggesting a depolarising role for the GABA(A) receptors. Treatment with KCl, which is known to depolarise membranes, prevented some of the decreased proliferation caused by inhibition of the GABA(A) receptors. This supported the depolarising role for the GABA(A) receptors. Inhibition of L-type voltage-gated Ca(2+) channels (VGCCs) reduced the proliferation in the same way as inhibition of the GABA(A) receptors. Inhibition of the channels increased the expression of the cyclin-dependent kinase inhibitor p27(KIP1), along with the reduced proliferation. These results are consistent with that when the membrane potential indirectly regulates cell proliferation with hyperpolarisation of the membrane potential resulting in decreased cell division. The increased expression of p27(KIP1) after inhibition of either the GABA(A) receptors or the L-type VGCCs suggests a link between the GABA(A) receptors, membrane potential, and intracellular Ca(2+) in regulating the cell cycle.